On the change in bacterial size and magnetosome features for magnetospirillum magnetotacticum (MS-1) under high concentrations of zinc and nickel - Kundu, S.; Kale, A. A.; Banpurkar, Arun G.; Kulkarni, G. R.; Ogale, S. B. (Biomaterials, 2009)
The characteristic size, shape and specific alignment of magnetite crystals synthesized by magnetotactic bacteria is a highly coordinated process with precise control over magnetosome vesicle formation, uptake and transport of Fe, and magnetite biomineralization. Magnetosome membranes along with some specific membrane proteins regulate crystal nucleation and morphology of magnetite. Several previous works have indicated that the morphology of mature magnetite crystals is largely unaffected by environmental conditions, though some recent studies have shown the possibility of manipulation of the biomineralization process. In this study we have examined the effects of high concentrations of Zinc and Nickel on the growth of Magnetospirillum magnetotacticum (MS-1) and the corresponding magnetosome formation. Using various characterizations it is shown that the growth of the bacterial cells, as well as the size, shape and magnetosome chain alignment is significantly influenced in the presence of high concentrations of Zn or Ni. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Biomineralization; magnetite; Magnetosome; Magnetospirillum magnetotacticum; Nickel; zinc